PENAFSIRAN TERHADAP KEDUDUKAN ALAT BUKTI DALAM PENYELESAIAN SENGKETA PERDATA DI PENGADILAN - Afriana, Anita (Jurusan Syariah dan Ekonomi Islam STAIN Parepare, 2013)
Formal judicial, law of evidence in Indonesia does not accommodate electronic documents as evidence, while in practice in Indonesia through e-commerce transactions has been widely used business transactions electronically. With further increase electronic activity, evidence that can be used by law should also include such information or documents electronically. Recognition of electronic information as evidence in court is still questionable validity. In the practice of the courts in Indonesia, the use of electronic data as valid evidence is virtually never existed, though in some countries, the electronic information recorded in electronic equipment has been taken into consideration in the judge decide a case, either criminal or civil. Practice it was not the party who filed the electronic evidence to face trial , except for criminal cases, so that the civil judge in the District Court, for example at the Bandung District Court decides there is no case which recognizes the electronic evidence as evidence that the same force with tool - proof evidence contained in Article 164 HIR. With this fact suggests that civil disputes generally in the District Court is not a dispute relating to the business and leads of electronic transactions. Evidence is not provided for in Article 164 HIR, can not be regarded as valid evidence. This is because the law of civil procedure is a formal legal binding. As the most powerful man in deciding a case , and is regarded as the person who can give vonnis van de rechter (judge s decision) , a judge granted flexibility to find the law (rechtsvinding), either by means of legal interpretation (wetinterpretatie) or by digging , following the and understand the legal values that live in the community. Legal theory lex specialis derogat lex generalis also be a reference judge in admitting electronic evidence as valid evidence, the law specifically waives the old law, Through the ITE Law, related to the strength of evidence of electronic evidence, the judges should be admitted as electronic evidence and legal evidence has the same probative force of evidence set forth in the HIR